Obtaining regulatory T cells from uraemic patients awaiting kidney transplantation for use in clinical trials. (4th July 2013) - Berglund, D.; Karlsson, M.; Biglarnia, A.‐R.; Lorant, T.; Tufveson, G.; Korsgren, O.; Carlsson, B.
Summary Adoptive transfer of regulatory T cells (Tregs) has been proposed for use as a cellular therapy to induce transplantation tolerance. Preclinical data are encouraging, and clinical trials with Treg therapy are anticipated. In this study, we investigate different strategies for the isolation and expansion of CD4+CD25highCD127low Tregs from uraemic patients. We use allogeneic dendritic cells (DCs) as feeder cells for the expansion and compare Treg preparations isolated by either fluorescence activated cell sorting (FACS) or magnetic activated cell sorting (MACS) that have been expanded subsequently with either mature or tolerogenic DCs. Expanded Treg preparations have been characterized by their purity, cytokine production and in‐vitro suppressive ability. The results show that Treg preparations can be isolated from uraemic patients by both FACS and MACS. Also, the type of feeder cells used in the expansion affects both the purity and the functional properties of the Treg preparations. In particular, FACS‐sorted Treg preparations expanded with mature DCs secrete more interleukin (IL)‐10 and granzyme B than FACS‐sorted Treg preparations expanded with tolerogenic DCs. This is a direct comparison between different isolation techniques and expansion protocols with Tregs from uraemic patients that may guide future efforts to produce clinical‐grade Tregs for use in kidney transplantation.